Psychologic morbidities prior to loop electrosurgical excision procedure in the treatment of cervical intraepithelial neoplasia. Issue 3 (1st April 2006) - Le, T.; Hopkins, L.; Menard, C.; Hicks-Boucher, W.; Lefebvre, J.; Fung, M. Fung Kee
Abstract : The objective of this study was to assess and compare anxiety and distress in patients undergoing colposcopic examinations and loop electrosurgical excision procedure (LEEP). Patients seen for evaluation of cervical intraepithelial neoplasia (CIN) and LEEP were recruited. All patients received further teaching with respect to their abnormality right after the colposcopic evaluation by nursing staff. The Hospital anxiety and Depression Scale (HADS) and the Psychosocial Effects of Abnormal Pap Smears (PEAPS) questionnaires were used to measure and compare distress between the two groups. Linear regression models were built to identify significant predictive variables for psychologic morbidities. Twenty-one colposcopy and 20 LEEP patients participated in this study. No significant demographic differences were noted. Eighty-one percent of patients having colposcopy and 65% of those undergoing LEEP can be classified as having significant anxiety and depression based on the HADS questionnaire. Patients undergoing LEEP scored significantly better than colposcopy patients on the mean total PEAPS score and on the self-belief/cancer concern and effects on sexual relationship dimension scores. Significant psychologic morbidities exist in patients diagnosed with CIN. Face-to-face individualized education and support after colposcopy can decrease patients' distress at subsequent treatment visits.